Evaluasi Penerapan Sistem Self Assessment Dalam Pemungutan Pajak Atas Barang dan Jasa Tertentu Atas Makanan dan / Atau Minuman (Pajak Restoran) Dalam Meningkatkan Pajak Daerah Di Kabupaten Sikka - Maria Yati Sonia Bria; Yosefina Andia Dekrita; Emilianus Eo Kutu Goo (Universitas Nusa Nipa Maumere, 2026)
This research aimed to evaluate the implemention of the self assessment system in the collection of taxes on certain goods and services no food and/or beverages (restaurant tax) in increasing local revenue in Sikka Regency. This research was based on the fact that the realization of restaurant tax revenue has not yet been optimal, which was caused by dishonesty amomg taxpayers in reporting their sales turnover. The research method used in techniques including interviews, observation, and document studies. The results of this research indicated that the evaluation of the implemention of the self assessment system in the collection of taxes on certain goods and services on food and/or beverages (restaurant tas) in creasing local revenue has been carried out following the provisions of the applicable regional regulations but has not yet been fully optimal. This was due to the challenges and constraints faced by the Regional Revenue Agency in collecting restaurant taxes. The challenges encountered include dishonesty among taxpayers in reporting their sales turnover, while the constraints include the low level of awareness and understanding of taxpayers regarding procedures for self-calculation, reporting, and payment. However, the Regional Revenur Agency has undertaken various efforts or strategies to increase restaurant tax revenue in Sikka Regency, such as conducting spot checks, implementing education and socialization programs, utilizing and installing technological tools such as M-Pos, and enforcing strict supervision to improve restaurant tax revenue targets and enchance local revenue in Sikka Regency, so that more optimal targets can be achievied